Sexual dimorphism of early transcriptional reprogramming in degenerating peripheral nerves - Chernov, Andrei V.; Shubayev, Veronica I. (Frontiers in Molecular Neuroscience, 2022)
Sexual dimorphism is a powerful yet understudied factor that influences the timing and efficiency of gene regulation in axonal injury and repair processes in the peripheral nervous system. Here, we identified common and distinct biological processes in female and male degenerating (distal) nerve stumps based on a snapshot of transcriptional reprogramming 24 h after axotomy reflecting the onset of early-phase Wallerian degeneration. Females exhibited transcriptional downregulation of a larger number of genes than males. RhoGDI, ERBB, and ERK5 signaling pathways increased activity in both sexes. Males upregulated genes and canonical pathways that exhibited robust baseline expression in females in both axotomized and sham nerves, including signaling pathways controlled by neuregulin and nerve growth factors. Cholesterol biosynthesis, reelin signaling, and synaptogenesis signaling pathways were downregulated in females. Signaling by Rho Family GTPases, cAMP-mediated signaling, and sulfated glycosaminoglycan biosynthesis were downregulated in both sexes. Estrogens potentially influenced sex-dependent injury response due to distinct regulation of estrogen receptor expression. A crosstalk of cytokines and growth hormones could promote sexually dimorphic transcriptional responses. We highlighted prospective regulatory activities due to protein phosphorylation, extracellular proteolysis, sex chromosome-specific expression, major urinary proteins, and genes involved in thyroid hormone metabolism. Combined with our earlier findings in the corresponding dorsal root ganglia (DRG) and regenerating (proximal) nerve stumps, sex-specific and universal early-phase molecular triggers of Wallerian degeneration enrich our knowledge of transcriptional regulation in peripheral nerve injury and repair.